The Adaptation of Building Information Modelling (BIM) on Existing IPD Pasir Mas As-Built Plan for Future Engineering References. Case Study: Blok Dewan Serbaguna - Mahiran, Nurmira Umairah; Zakaria, Muhammad Nizam; M. Shahrulmizi Ab. Manaf (Recent Trends in Civil Engineering and Built Environment, 2024)
Building Information Modelling (BIM) is the new technology used in construction industry. It is increasingly known as the best alternative in the construction firm that would replacing the conventional method. BIM is tools of information management that has been used by Architecture, Engineering and Construction (AEC) industries in Malaysia. BIM are commonly implemented in a new building project because the process is easy rather than to the existing building. Therefore, most of existing buildings have not been implemented with BIM yet, make it difficult for engineers to refer to most existing buildings in the future. In recent years, the implementation of BIM on existing buildings has received growing attention. The aim of this study is to provide the information on existing building through BIM implementation for future engineering references. Therefore, the case study will conducted on existing building of “Blok Dewan Serbaguna, IPD Pasir Mas”. This study also carried out to compare the analysis results of the building with existing as-built drawing. A literature review was done to explore the information regarding the implementation of BIM on existing building, definitions of BIM,uses of BIM, BIM tools in construction projects as well as benefits of BIM. This study conducted using tools of BIM software which are Tekla Structural Designer for analysis and design structure, and Autodesk Revit for modelling the building. Therefore, these software will produce accurate detailed documentation of steel and concrete designs, as well as provide detailed information of the existing building for future engineering references